Comparison between single- and double-bundle anterior cruciate ligament reconstructions for knee with grade 2 medial collateral ligament injury - Chen, Lian-Xu (Medicine (Baltimore), 2021)
This research discussed clinical outcomes of anterior cruciate ligament reconstruction accompanied by conservative treatment for grade 2 medial collateral ligament injury, and comparison was performed between double-bundle and single-bundle anterior cruciate ligament reconstruction. Clinical information was retrospectively collected for 41 cases suffering anterior cruciate ligament injuries accompanied by grade 2 medial collateral ligament injuries. Within 14 days after their injuries 22 cases received single-bundle anterior cruciate ligament reconstruction (SB group), while 19 were treated with double-bundle medial collateral ligament reconstruction (DB group). Physical statuses were estimated based on International Knee Documentation Committee (IKDC) and Lysholm scores, Lachman, pivot shift and manual valgus test, and range of motion (ROM), while side-to-side difference was estimated through KT 2000 arthometer. Anterior cruciate ligament reconstruction accompanied by conservative treatment showed significantly improved anteroposterior, rotational and valgus stability, and IKDC and Lysholm scores (in comparison to pre-operative status, P < .05). Incidence of pivot shift was dramatically lower in DB group (2/19) than in SB group (7/22 and 2/22; P = .028). No substantial dissimilarity existed between DB and SB groups either in Lachman and valgus tests, KT 2000, ROM, IKDC, or Lysholm scores. Anterior cruciate ligament reconstruction accompanied by conservative treatment could achieve outstanding stability and functional manifestations for cases facing anterior cruciate ligament injury accompanied by grade 2 medial collateral ligament injury. Moreover, double-bundle anterior cruciate ligament reconstruction is superior to single-bundle operation in treating rotational instability of the knee. Level of evidence: Retrospective comparative study, Level III.